2020
DOI: 10.1002/ajcp.12479
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Incidents and Experiences of Racism and Sexism: Examining Associations with Components of Critical Consciousness for System‐Involved Girls of Color

Abstract: Scholarship identifies critical consciousness as a key developmental asset in promoting the well‐being of adolescents experiencing multiple socio‐structural axes of oppression. Girls of color at acute risk for legal system involvement or re‐involvement are absent from this literature. They are a critical population in which to examine this construct given their experiences of oppression and the myriad benefits of critical consciousness. The current study addresses this gap by examining traumatic incidents and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Importantly, in our study critical reflection was a significant mediator of the relation between school racial socialization messages and critical action, which suggests that our Black and Latinx youths' actions were explained in part by their increasing awareness of inequality in society (Diemer et al., 2016; Singh et al., 2021). Previous research has supported the idea of the school context as an important space for the development of critical consciousness (Heberle et al., 2020; Seider et al., 2017, 2020) and has found that critical reflection functions as a mediator between adolescents' experiences and critical action (Hope et al., 2020; Tyler et al., 2020).…”
Section: Discussionmentioning
confidence: 60%
“…Importantly, in our study critical reflection was a significant mediator of the relation between school racial socialization messages and critical action, which suggests that our Black and Latinx youths' actions were explained in part by their increasing awareness of inequality in society (Diemer et al., 2016; Singh et al., 2021). Previous research has supported the idea of the school context as an important space for the development of critical consciousness (Heberle et al., 2020; Seider et al., 2017, 2020) and has found that critical reflection functions as a mediator between adolescents' experiences and critical action (Hope et al., 2020; Tyler et al., 2020).…”
Section: Discussionmentioning
confidence: 60%
“…Other contexts youth are exposed to most often do not encourage these forms of analysis and action. For example, girls involved in the juvenile legal system reported more critical action in response to experiences with sexism and racism, but not greater critical reflection—likely because this context was invested in punishing them rather than encouraging their interrogation of oppression (Singh et al, 2021). Thus, it is likely that in facilitating critical dialogue about oppression, providing opportunities for critical action, and engaging youth democratically as experts of their lived experience, community‐based activism supports the development of CC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, experiencing discrimination can lead the adolescent down a path of critical reflection (Tyler et al, 2020). Among a sample of majority Latinx female adolescents, Singh et al (2021) found that experiences of racism were positively associated with critical action but not critical reflection. Similarly, in a study of Black and Latinx adolescents, results revealed that discrimination predicted higher public prosocial behavior for Latinx adolescents.…”
Section: The Role Of Discrimination and Messages From Peers Media And...mentioning
confidence: 99%